2008
DOI: 10.1007/s00264-008-0712-y
|View full text |Cite
|
Sign up to set email alerts
|

Are “knife and fork” good enough for day case surgery of resistant tennis elbow?

Abstract: This observational retrospective study was performed on 22 consecutive patients treated surgically in a day surgery unit for resistant tennis elbow to ascertain the effectiveness of the "knife and fork" procedure. All patients had an unfavourable response to nonsurgical treatment lasting at least six months. A simple and inexpensive "knife and fork" technique yielded excellent results in 90.5% of patients and a high percentage (95.2%) of satisfied patients at an average follow-up of two years. There were no fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We do not consider this to be a problem as the surgical technique used in our study does not include removal of tendinous tissue. In outcome studies with an observation period averaging 2 years or more, a good or excellent outcome has been reported in over 80% of the patients by both the Nirschl surgical technique or modifications of the latter that includes removal of degenerative tendinous tissue [ 11 , 12 , 25 ] and the Hohmann extensor release without removal of degenerative tendinous tissue [ 27 , 33 ]. Further, there is no correlation between the intensity of the histologic reaction and the clinical outcome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We do not consider this to be a problem as the surgical technique used in our study does not include removal of tendinous tissue. In outcome studies with an observation period averaging 2 years or more, a good or excellent outcome has been reported in over 80% of the patients by both the Nirschl surgical technique or modifications of the latter that includes removal of degenerative tendinous tissue [ 11 , 12 , 25 ] and the Hohmann extensor release without removal of degenerative tendinous tissue [ 27 , 33 ]. Further, there is no correlation between the intensity of the histologic reaction and the clinical outcome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the efficacy and safety of open procedures for the treatment of LE. 79 – 82 Dwyer et al found that greater than 95% of LE patients reported satisfaction with the open approach at 2 years follow-up. 82 Dunn et al demonstrated sustained high long-term satisfaction rates for 44 patients, with a 97% improvement rate and a 3% rate of revision at an average of 12.6 years of follow-up after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…79 – 82 Dwyer et al found that greater than 95% of LE patients reported satisfaction with the open approach at 2 years follow-up. 82 Dunn et al demonstrated sustained high long-term satisfaction rates for 44 patients, with a 97% improvement rate and a 3% rate of revision at an average of 12.6 years of follow-up after surgery. 81 These studies support the findings that an open surgical approach is highly effective for treating refractory LE cases.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, open surgical debridement of extensor tendons with or without suture anchor repair provides high rates (95%-97%) of patient satisfaction with minimal complications in refractory cases of lateral epicondylitis. 17,18,48 However, a recent randomized controlled trial showed no additional benefit of excision of diseased extensor carpi radialis brevis tendon compared with sham surgery. 27 Conflicting results have been observed in surgical treatment of other tendinopathies as well, with patient satisfaction ranging from 69% to 100% and complication rates varying from 0% to 85%.…”
mentioning
confidence: 99%